Lost Land - Eyk, Manfred van; Hanrath, Caroline (VPRO, 1998)
Soros Documentary Fund In the north of Russia, the crude oil industry leaves behind polluted rivers and forests while inhabitants are relocated by force. A team of anthropologist travel to Ugut to investigate the gradual disappearance of the Khanty people in Western Siberia. They investigate the reasons behind the slow but steady extinction of the indigenous population in Siberia.